Web-Based Car Rental And Cab Service System For Ump Students (Umpcab) - Nur Hasya, Mohd Nordin (2022)
A web-based system also known as a web application is an application that is invoked with a Web browser over the Internet. It is stored on a remote server and delivered over the Internet through a browser interface. In just one decade, the Web has evolved from being a repository of pages used primarily for accessing static, mostly scientific, information to a powerful platform for application development and deployment. Compared to mobile applications, web applications are much easier to use. This is because mobile application usually requires user to have a certain amount of storage for them to be able to use the application. Web application on the other hand does not require users’ storage to function because it is stored on a remote server and delivered over the Internet. Besides, not everyone has the storage capacity to store multiple applications in their smartphones. By using web application, it can both be accessed through the smartphone and also other devices through the browser. This application consists of two modules which are Car Rental and Cab Service. Three existing application of car rental has been reviewed to produce a better version of car rental application. RAD model has been chosen for the development of this project. There are five phases involved in the model to make sure that the application developed achieves the proposed objectives. The application was evaluated and tested by the UMP students to investigate its effectiveness and user perception towards the application. The result showed that the students give positive feedbacks and they agree that this application can help them experience a better way of renting for cars and booking for cab services.